Assessment of US Hospital Compliance With Regulations for Patients’ Requests for Medical Records - Lye, Carolyn T. (JAMA Netw Open, 2018)
IMPORTANCE: Although federal law has long promoted patients’ access to their protected health information, this access remains limited. Previous studies have demonstrated some issues in requesting release of medical records, but, to date, there has been no comprehensive review of the challenges that exist in all aspects of the request process. OBJECTIVE: To evaluate the current state of medical records request processes of US hospitals in terms of compliance with federal and state regulations and ease of patient access. DESIGN, SETTING, AND PARTICIPANTS: A cross-sectional study of medical records request processes was conducted between August 1 and December 7, 2017, in 83 top-ranked US hospitals with independent medical records request processes and medical records departments reachable by telephone. Hospitals were ranked as the top 20 hospitals for each of the 16 adult specialties in the 2016-2017 US News & World Report Best Hospitals National Rankings. EXPOSURES: Scripted interview with medical records departments in a single-blind, simulated patient experience. MAIN OUTCOMES AND MEASURES: Requestable information (entire medical record, laboratory test results, medical history and results of physical examination, discharge summaries, consultation reports, physician orders, and other), formats of release (pick up in person, mail, fax, email, CD, and online patient portal), costs, and request processing times, identified on medical records release authorization forms and through telephone calls with medical records departments. RESULTS: Among the 83 top-ranked US hospitals representing 29 states, there was discordance between information provided on authorization forms and that obtained from the simulated patient telephone calls in terms of requestable information, formats of release, and costs. On the forms, as few as 9 hospitals (11%) provided the option of selecting 1 of the categories of information and only 44 hospitals (53%) provided patients the option to acquire the entire medical record. On telephone calls, all 83 hospitals stated that they were able to release entire medical records to patients. There were discrepancies in information given in telephone calls vs on the forms between the formats hospitals stated that they could use to release information (69 [83%] vs 40 [48%] for pick up in person, 20 [24%] vs 14 [17%] for fax, 39 [47%] vs 27 [33%] for email, 55 [66%] vs 35 [42%] for CD, and 21 [25%] vs 33 [40%] for online patient portals), additionally demonstrating noncompliance with federal regulations in refusing to provide records in the format requested by the patient. There were 48 hospitals that had costs of release (as much as $541.50 for a 200-page record) above the federal recommendation of $6.50 for electronically maintained records. At least 6 of the hospitals (7%) were noncompliant with state requirements for processing times. CONCLUSIONS AND RELEVANCE: The study revealed that there are discrepancies in the information provided to patients regarding the medical records release processes and noncompliance with federal and state regulations and recommendations. Policies focused on improving patient access may require stricter enforcement to ensure more transparent and less burdensome medical records request processes for patients.